Photobiomodulation Therapy for the Management of Patients With Inferior Alveolar Neurosensory Disturbance Associated With Oral Surgical Procedures: An Interventional Case Series Study: Photobiomodulation THERAPY for Inferior Alveolar Neurosensory Disturbance - Hakimiha, Neda; Rokn, Amir Reza; Younespour, Shima; Moslemi, Neda (Journal of Lasers in Medical Sciences, 2020)
Introduction:: Inferior alveolar nerve (IAN) injury is a serious complication during intraoral surgeries. We aimed to evaluate the outcome of photobiomodulation (PBM) therapy in patients with IAN injury associated with third molar or implant procedures. Methods: Eight patients with alteration of sensory function of the IAN after third molar or implant surgeries were enrolled in this case series study. The patients received 10 sessions of PBM therapy (810 nm diode laser, 200 mW, 10 J/cm2 per point, three times a week). Pinprick (PP) and visual analog scale (VAS) neurosensory tests were recorded at each treatment session and 14 days after the last treatment. Results: The median percentage change of outcomes from first to last visit was as follows: VAS score: +125.00% (range: 50.00 to 166.67); PP score: +350% (range: 150 to 800). The duration of paresthesia was inversely correlated with changes of VAS and PP scores. No significant association was found between the gender or age of patients and changes in VAS and PP scores. Conclusion: Considering the limitations of this study, PBM with the parameters used in this study presented positive effects on neurosensory recovery in patients suffering from IAN injury associated with routine intraoral procedures. Patients with a shorter duration of paresthesia tended to respond more favorably to PBM therapy.